Thermal Acclimation to the Highest Natural Ambient Temperature Compromises Physiological Performance in Tadpoles of a Stream-Breeding Savanna Tree Frog - Longhini, Leonardo S.; Zena, Lucas A.; Polymeropoulos, Elias T.; Rocha, Aline C. G.; da Silva Leandro, Gabriela; Prado, Cynthia P. A.; Bícego, Kênia C.; Gargaglioni, Luciane H. (Frontiers in Physiology, 2021)
Amphibians may be more vulnerable to climate-driven habitat modification because of their complex life cycle dependence on land and water. Considering the current rate of global warming, it is critical to identify the vulnerability of a species by assessing its potential to acclimate to warming temperatures. In many species, thermal acclimation provides a reversible physiological adjustment in response to temperature changes, conferring their resilience in a changing climate. Here, we investigate the effects of temperature acclimation on the physiological performance of tadpoles of a stream-breeding savanna tree frog (Bokermannohyla ibitiguara) in relation to the thermal conditions naturally experienced in their microhabitat (range: 18.8-24.6°C). We quantified performance measures such as routine and maximum metabolic rate at different test (15, 20, 25, 30 and 34°C) and acclimation temperatures (18 and 25°C). We also measured heart rate before and after autonomic blockade with atropine and sotalol at the respective acclimation temperatures. Further, we determined the critical thermal maximum and warming tolerance (critical thermal maximum minus maximum microhabitat temperature), which were not affected by acclimation. Mass-specific routine and mass-specific maximum metabolic rate, as well as heart rate, increased with increasing test temperatures; however, acclimation elevated mass-specific routine metabolic rate while not affecting mass-specific maximum metabolic rate. Heart rate before and after the pharmacological blockade was also unaffected by acclimation. As a result, aerobic scope in animals acclimated to 25°C was substantially reduced, suggesting that physiological performance at the highest temperatures experienced in their natural habitat is compromised. In conclusion, these data suggest that the tadpoles of B. ibitiguara, living in a thermally stable environment, have a limited capacity to physiologically adjust to the highest temperatures found in their micro-habitat, making the species more vulnerable to future climate change.